Analysis of the Principles of Communication in the Perspective of the Qur'an - Putra, Fauzi Eka; Nofrianti, Mami (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
The task of communication is to bring people closer to their neighbors and their Creator by applying the principles in the Qur'an in everyday life. For this method of research using library research the nature of this research is descriptive analysis, with the process of data collection using written studies and data analysis this research utilizes the scientific relationship between the principles of communication in the Qur'an that are adapted to the modern era. Thus, the results of this study suggest that the eight principles of communication from the perspective of the Quran can be applied in the current context if the communicators and communicators can understand those principles well and adapt to the existing reality.